Association of Circulating Long Noncoding 7S RNA with Deep Vein Thrombosis - Wang, Xiao; Memon, Ashfaque A.; Hedelius, Anna; Grundberg, Anton; Elf, Johan L.; Svensson, Peter J.; Sundquist, Jan; Sundquist, Kristina (Seminars in Thrombosis and Hemostasis, 2023)
Mitochondrial dysfunction is a recognized factor in the pathogenesis of deep vein thrombosis (DVT). The role of 7S RNA, a long noncoding RNA that plays an important role in mitochondrial function, in DVT remains unclear. In this study, we aimed to investigate the potential use of 7S RNA as a biomarker in DVT. Plasma samples were obtained from 237 patients (aged 16–95 years) with suspected DVT recruited in a prospective multicenter management study (SCORE) where 53 patients were objectively confirmed with a diagnosis of DVT and the rest were diagnosed as non-DVT. 7S RNA was measured using quantitative real-time polymerase chain reaction in plasma samples. The plasma expression of 7S RNA was significantly lower in DVT compared with non-DVT (0.50 vs. 0.95, p = 0.043). With the linear regression analysis, we showed that the association between the plasma expression of 7S RNA and DVT (β = −0.72, p = 0.007) was independent of potential confounders. Receiver-operating characteristic curve analysis showed the area under the curve values of 0.60 for 7S RNA. The findings of the present study showed a notable association between 7S RNA and DVT. However, further investigations are needed to fully elucidate the exact role of 7S RNA in the pathophysiology of DVT and its diagnostic value.
Keywords: long noncoding RNA; 7S RNA; venous thromboembolism; deep venous thrombosis; diagnosis